Exploring the Potentials of Integrating Immersive Virtual Reality (VR) Into Neuroanatomy Education - Putri Alief Siswanto; Indra Pramanasari; Ni Luh Bella Dwijaksara; Agrippina Waya Rahmaning Gusti (Sriwijaya Journal of Medicine, 2024)
Neuroanatomy teaching requires students to understand complex spatial relations of the brain structures, traditionally accomplished using a cadaver. However, dissecting neuroanatomical structures remains a challenge due to their intricate nature. Digital technology is increasingly being adopted as a three-dimensional (3D) visualization tool, and immersive virtual reality (VR) has attracted great interest. A literature review was conducted using EMBASE, MEDLINE, Web of Science, Scopus, and ProQuest databases. Studies published from 2015 onwards that compared VR-based neuroanatomy teaching with traditional methods were included. Only English-language, peer-reviewed articles with quantitative learning outcomes were analyzed. This review included 6 studies and suggests that VR is non-inferior to other teaching methods and performs better in spatial-related questions. VR is also favored to increase student motivation and engagement. These positive learning experiences are expected to diminish neurophobia. Meanwhile, as a novel technology, challenges for incorporating VR into neuroanatomy education include costly technical requirements, inadequate image resolution, anatomy details, absence of texture perception, and health concerns such as cyber-sickness. Future studies should employ a large sample size (>100), assess participants' working memory and spatial abilities, conduct longer experiment duration, and examine long-term retention. Digital simulation through VR is also attainable and can be implemented further for neurosurgical training. As technology advances, immersive VR technology can potentially be an effective teaching tool for neuroanatomy.